KESELAMATAN PELAYARAN KAPAL PADA PT JAKARTA INTERNATIONAL CONTAINER TERMINAL TANJUNG PRIOK - Asep Ali Thabah; Abdul Hafidh Saputra; Hanifah Hanifah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
PT Jakarta International Container Terminal (JICT) is a subsidiary of PT (Persero) Pelabuhan Indonesia II (Pelindo II) and its business activities is the service of loading / unloading of export / import containers. The purpose of this research is to find out the role of Verified Gross Mass (VGM) system in maintaining the safety of vessel shipping. Theresearch method used descriptive qualitative. Implementation of Verified Gross Mass (VGM) system at PT. JICT has been running well in accordance with the provisions that have been established using the sensor technology called Weight in Motion (WIM). The advantage of this system is to minimize misunderstanding in the placement of containers on board by Planner. The role of the Verified Gross Mass (VGM) system in safeguarding cruise shipping is closely related. With this system, the information on the amount of container gross weight will be much clearer, precisely accurate so that the possibility of a ship accident caused by the inaccuracies of containers resulting in unstable ships can be suppressed.